Optimization of GIS-Based Evacuation Routes for Mitigating Mount Merapi Eruption in Wukirsari Village, Sleman - Bagaskara, Muhammad Abdiel; Herika Muhamad Taki; Anita Sitawati Wartaman (Journal of Synergy Landscape, 2025)
Mount Merapi is one of Indonesia's most active volcanoes, posing a persistent threat to surrounding communities. Wukirsari Village, located in Cangkringan District, is among the areas most vulnerable to volcanic eruptions due to its proximity to active river channels and its inclusion in high-risk volcanic hazard zones. This study aims to identify and assess alternative evacuation routes that meet the safety standards set by Indonesia’s National Disaster Management Agency. A quantitative approach was employed, using spatial analysis techniques through Geographic Information Systems (GIS) and the Network Analyst extension in ArcGIS. Five core parameters guided the route evaluation: route length, road width, direction away from the hazard source, presence of river obstacles, and estimated evacuation time. The findings indicate that among the three routes analyzed, the path to Barak Desa Wukirsari was the most optimal. It offers the shortest distance (0.82 km), the fastest travel time, and avoids both river crossings and the highest hazard zones (Kawasan Rawan Bencana III - Zone III of the Hazardous Area). This research contributes meaningfully to spatial disaster mitigation planning, particularly for volcanic-prone regions. The outcomes are expected to serve as practical references for local governments, disaster management agencies, and communities in designing responsive and safe evacuation infrastructure to enhance preparedness and reduce risk in future volcanic emergencies.